Development of enzyme immunoassay for quantitation of mycelial biomass in Brassica genotypes against Alternaria blight (Journal of Oilseed Brassica, 2026)
Brassica crops faces a major infestation of Alternaria brassicae, a causal agent of Alternaria blight. Adopted chemical methods for controlling Alternaria infestation are ineffective and environmentally challenging. To bypass these challenges, strategies of enhancing innate immunity of Brassica plant resistance to pathogen, or suppression of virulence seems promising. For suppression of virulence early detection of pathogen, before symptom appearance is the main limitation. Efficient disease management appropriately buffered with resistance disease programmme depends largely on the reliable identification and characterization of fungal isolate. Therefore, there is a need to develop a potential tool for immunological characterization of isolates of A. brassicae. Polyclonal antibody against total mycelia of A. brassicae was generated to develop ELISA based method for early detection and quantitation of mycelial biomass. Total protein was extracted from pathogen inoculated Brassica leaves (Varuna and PAB 9511) during different time interval of infection. The quantitative estimation of mycelial biomass of A. brassicae was estimated by indirect ELISA using polyclonal antiserum. When compared with healthy control, pathogen was not detected in the susceptible cultivar Varuna until after 6 h of post-inoculation. It was also observed that among the inoculated genotypes of Brassica, mycelium biomass was increased with disease progression in susceptible cultivar (Varuna), while the tolerant cultivar (PAB 9511) contained less. This demonstrated the efficacy of adopted immunological technique as a potent tool for detection, quantitation of mycelial biomass for characterization of differential tolerance against Alternaria blight in Brassica genotypes.